Open a new window in the world of circulating microRNAs by merging ChemiRNA Tech with a Luminex platform. Issue 6 (5th October 2022) - Marín-Romero, Antonio; Tabraue-Chávez, Mavys; Dear, James W.; Díaz-Mochón, Juan José; Pernagallo, Salvatore
Abstract : miRNA analysis simplified using multi-ChemiRNA Tech. Abstract : microRNAs are small noncoding RNA molecules showing huge promise as biomarkers and diagnostic tools for illnesses, as significant changes in their expression occur in response to pathological states. However, multiplex detection of microRNAs represents a major challenge towards the use of microRNA signatures. Hence, our group has tackled this need by developing an accurate and PCR-free approach to detect multiple microRNAs in serum samples. ChemiRNA Tech has been refined to be merged with a Luminex xMAP system. The combination of these two technologies has created a unique bead-based multiplex assay capable of simultaneously measuring miR-122-5p, miR-451a-5p and miR-193a-5p in only 10 μL of serum. This novel multiplex assay for the direct quantitative measurement of circulating microRNA signatures offers benefits over gold standard singleplex assay techniques in terms of cost, time savings and ease of use.